A survey for the rare blood group antigen variants, En(a-), Gerbich negative and Duffy negative on Espiritu Santo, Vanuatu in the South Pacific. - Brindle, P; Maitland, K; Williams, T; Ganczakowski, M (1995)
The people of Vanuatu exhibit several different genetic red cell polymorphisms. Some of these, such as alpha thalassaemia, are thought to have reached a high frequency as a result of selection pressure by malaria. In this study three rare blood group antigen variants, En(a-), Gerbich negative and Duffy negative, which are thought to confer a protective effect against malaria were sought in a sample of 214 (187 in the case of Duffy) from Espiritu Santo, Vanuatu. No individuals bearing these rare variants were found. The original settlers in Vanuatu are thought to have migrated from Papua New Guinea some 5,000 years ago, so it is of interest to note that no individuals were found to be Gerbich negative despite a high frequency in Melanesians living on some coastal parts of Papua New Guinea.